A Statistical Study on the Properties of Dips Ahead of Dipolarization Fronts Observed by MMS. Issue 1 (12th January 2019) - Schmid, D.; Volwerk, M.; Plaschke, F.; Nakamura, R.; Baumjohann, W.; Wang, G. Q.; Wu, M. Y.; Zhang, T. L.
Abstract: Magnetic reconnection in the magnetotail accelerates plasma in short‐duration bursts of fast flows, referred to as bursty bulk flows toward the Earth. These bursty bulk flows are typically accompanied by a sharp increase in the northward magnetic field component, the so‐called dipolarization front (DF). This rapid increase in northward magnetic field is often preceded by a decrease, the so called DF‐dip, where the northward magnetic field component sometimes even changes sign and turns southward. Here we present a statistical study of the DF‐dip of 43 events, using observations from the Magnetospheric Multiscale (MMS) mission during summer 2017, when MMS's apogee was located in the magnetotail around 25  R E . The 43 events are subdivided into two categories according to their DF‐dip: 20 events where the DF‐dip stays northward (positive DF‐dip category) and 23 events where the DF‐dip turns fully southward (negative DF‐dip category). We find that (1) the magnetic field depression ahead of the DF of the positive DF‐dip events correlates mainly with perpendicular currents and diamagnetic currents flowing ahead of the DF and (2) the magnetic field depression ahead of the DF of the negative DF‐dip events correlates mainly with field‐aligned currents and that this type of events might be (a) earthward moving flux rope‐like structures caused by multiple X‐line reconnection and/or (b) are a result of localized, single X‐line reconnection under a guide field. Plain Language Summary: When magnetic field lines in the Earth's magnetotail reconnect, they shoot earthward like a stretched elastic band. The plasma, connected to the magnetic field, is thereby accelerated. This usually happens repeatedly on short timescales and is called a bursty bulk flow. The reconnected field lines have a more vertical direction, instead of the original horizontal orientation. When the bursty bulk flow crosses over the spacecraft, we see a rapid increase in the vertical (northward) magnetic field component, referred to as dipolarization front, which is usually preceded by a small decrease, the so‐called dipolarization front‐dip. This decrease comes in two categories, one where vertical magnetic field component remains positive (northward) and one where the vertical magnetic field component changes its sign and becomes negative (southward). It is shown that these are two separate categories with different origins. Key Points: Size of the magnetic field depression ahead of DF correlates with field‐aligned currents if the depression is negative (negative DF‐dip) Size of the magnetic field depression ahead of DF correlates with perpendicular currents if the depression stays positive (positive DF‐dip) Positive DF‐dip events are found closer to flow braking region than negative DF‐dip events